Levels of Cholesterol in Small LDL Particles Predict Atherosclerosis Progression and Incident CHD in the HDL-Atherosclerosis Treatment Study (HATS) - Williams, Paul T. (Public Library of Science, 2013)
OBJECTIVE: Test whether angiographically-documented changes in percent stenosis and clinical endpoints (coronary-related deaths, myocardial infarctions, stroke, revascularization for worsening ischemia) in the HDL-Atherosclerosis Treatment Study (HATS) were attributable to specific LDL-subclasses. METHODS: Gradient gel electrophoresis of on-study LDL-subclass cholesterol concentrations were measured in 32 placebo, 33 simvastatin-niacin, 38 antioxidant, and 39 simvastatin-niacin & antioxidant treated participants. The prespecified primary end point was the mean change per patient from the initial arteriogram to the final arteriogram in the percent stenosis caused by the most severe lesion in each of the nine proximal coronary segments. RESULTS: The change in the percent stenosis of the most severe proximal lesions increased in association with higher concentrations of the small LDL subfractions LDL-IIIb (24.2–24.6 nm) and LDL-IVa (23.3–24.1 nm) before (both P = 0.002) and after (P = 0.01 and P = 0.03 respectively) adjustment for treatment group and on-study HDL-cholesterol, LDL-cholesterol, and triglyceride concentrations. The associations appeared specific to lesions with <30% baseline stenosis. When adjusted for age, sex, baseline BMI and cigarette use, the odds for primary clinical endpoints (death from coronary causes, nonfatal myocardial infarction, stroke, or revascularization for worsening ischemia) were significantly greater in subjects with higher on-study LDL-IIIb levels both before (P = 0.01) and after (P = 0.03) adjustment for treatment group and the standard lipid values. CONCLUSIONS: Plasma LDL-IIIb cholesterol concentrations were related to changes in coronary artery stenosis and cardiovascular events in patients with coronary artery disease and low HDL-cholesterol. TRIAL REGISTRATION: ClinicalTrials.gov NCT00000553